2015
DOI: 10.1108/oir-05-2015-0152
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of mobile social networking sites for learning?

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:123705 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 95 publications
(57 citation statements)
references
References 62 publications
(73 reference statements)
4
51
1
Order By: Relevance
“…The students formed their perceptions of the use of digital technologies in their formal learning based on their experiences of the use of such technologies in their personal and social lives as well as the use of these technologies in informal learning. The findings aligned with findings of similar studies that showed students had positive perceptions about the use of digital technologies in their formal learning, examples of these digital technologies include mobile devices (Kim, et al, 2013); mobile SMS (Wong, et al, 2015), online social networking (Hamid, et al, 2015) and general ICT (Waycott et al, 2010;Makura 2014). The findings suggest that students would accept the use of digital technologies in their formal learning.…”
Section: Students' Perceptions Of the Use Digital Technologies In Thesupporting
confidence: 76%
See 1 more Smart Citation
“…The students formed their perceptions of the use of digital technologies in their formal learning based on their experiences of the use of such technologies in their personal and social lives as well as the use of these technologies in informal learning. The findings aligned with findings of similar studies that showed students had positive perceptions about the use of digital technologies in their formal learning, examples of these digital technologies include mobile devices (Kim, et al, 2013); mobile SMS (Wong, et al, 2015), online social networking (Hamid, et al, 2015) and general ICT (Waycott et al, 2010;Makura 2014). The findings suggest that students would accept the use of digital technologies in their formal learning.…”
Section: Students' Perceptions Of the Use Digital Technologies In Thesupporting
confidence: 76%
“…Their attitudes did not differ based on their gender and computer experience, but they did differ based on their ability to use computer programs. Wong, Tan, Loke, and Ooi (2015) examined the factors that influence users' intentions to use mobile SMS to facilitate their learning; they found that performance expectancy, effort expectancy, learning compatibility, reachability, and convenience all had significant influences on intentions to use. In a more recent study, Baturay, Gökçearslan, and Ke (2017) examined the factors that influence students' intentions of accepting technology.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the sampling locations were selected from the list of five large shopping malls in Klang Valley ( Chin, 2018 ). The reason being was that high traffic of consumers with different demographics are present in shopping malls ( Wong et al, 2015 ; Tan and Ooi, 2018 ). Additionally, the timing of the data collection varied in order to prevent sample bias ( Hew et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…Current studies on exploring the conventional use of these tools for daily SIs cannot explain the behavior of individuals to adopt them for learning purposes (Tan, Ooi, Sim, & Phusavat, 2012; R.-B. Wang & Du, 2014; C.-H. Wong, Tan, Loke, & Ooi, 2015). Consequently, it is important to explore the factors that influence users to adopt mobile Web 2.0 learning (MW2.0L).…”
Section: Introductionmentioning
confidence: 99%